O-027 In-hospital mortality and short-term clinical outcome in octo- and non-agenarian patients with aneurysmal subarachnoid hemorrhage treated endovascularly at a tertiary referral medical center. (4th July 2012) - Almandoz, J Delgado; Crandall, B; Fease, J; Kadkhodayan, Y; Scholz, J; Anderson, R; Lockhart, K; Mowbray-Donahue, T; Dyste, G; Tubman, D
Abstract : Purpose: To determine the in-hospital mortality and short-term clinical outcome in a cohort of octo- and non-agenarian patients with aneurysmal subarachnoid hemorrhage (SAH) treated endovascularly at a tertiary referral medical center. Methods: We retrospectively identified all octo- and non-agenarian patients with aneurysmal SAH who were treated endovascularly at our institution from January 1, 1997 until December 31, 2011. We reviewed the (1) medical records to determine patient age, gender, admission Hunt-Hess scale (HHS), periprocedural complications, length of hospital stay, in-hospital mortality and modified Rankin Scale (mRS) at hospital discharge among survivors, and (2) treatment catheter angiograms to determine aneurysm location, maximum dimension and immediate post-treatment Raymond scale. Good clinical outcome was defined as an mRS 0–3 at hospital discharge. Results: A total of 23 octo- and non-agenarian patients had aneurysmal SAH and were treated endovascularly at our institution during our study's 15-year time period. Twenty patients were female (87%) and 3 male (13%), with a mean age of 84.2 years (median 83 years, range 80–97 years). Admission HHS was 1–2 in 5 patients (21.7%), three in eight patients (34.8%) and 4–5 in 10 patients (43.5%). Aneurysm locations were: six in the posterior communicating artery (26.1%), five in the middle cerebral artery (21.7%), four in the anterior communicating artery (17.4%), two in the basilar artery (8.7%), two in the internal carotid artery (8.7%), two in the posterior inferior cerebellar artery (8.7%), one in the superior cerebellar artery (4.3%) and one in the vertebral artery (4.3%). Mean maximum aneurysm sac dimension was 6.5 mm (median 5 mm, range 3–14 mm). Immediately post-treatment, 16 patients had complete aneurysm occlusion (69.6%), six had a neck remnant (26.1%) and one had residual aneurysm sac filling (4.3%). Thromboembolic complications occurred in four patients (17.4%), leading to a cerebral infarction in 1 patient (4.3%). Mean length of hospital stay was 14.6 days (median 12 days, range 3–30 days). In-hospital mortality was 30.4%. Among the 16 survivors, there was a 50% chance of a good clinical outcome at hospital discharge (mRS 0–3). There was a statistically-significant difference in the likelihood of a good clinical outcome at hospital discharge (mRS 0–3) between the five patients with admission HHS of 1–2 (80%) and the 18 patients with admission HHS of 3–5 (22.2%, p value 0.033, Abstract O-027 table 1 ). Conclusion: In-hospital mortality was relatively low (30.4%) and there was a fair chance of a good clinical outcome at hospital discharge among survivors (50%) in our cohort of octo- and non-agenarian patients with aneurysmal SAH treated endovascularly. Furthermore, patients with admission HHS 1–2 had no in-hospital deaths and demonstrated a significantly higher likelihood of an overall good clinical outcome at hospital discharge (80%) compared to patients with admission HHS 3–5 (22%). Competing interests: None.